Innovative methods for remote assessment of neurobehavioral development. (December 2021) - Gustafsson, Hanna C.; Young, Anna S.; Stamos, Gayle; Wilken, Sydney; Brito, Natalie H.; Thomason, Moriah E.; Graham, Alice; Nigg, Joel T.; Sullivan, Elinor L.
Abstract: In response to the COVID-19 pandemic, research institutions across the globe have modified their operations in ways that have limited or eliminated the amount of permissible in-person research interaction. In order to prevent the loss of important developmentally-timed data during the pandemic, researchers have quickly pivoted and developed innovative methods for remote assessment of research participants. In this manuscript, we describe methods developed for remote assessment of a parent child cohort with a focus on examining the perinatal environment, behavioral and biological indicators of child neurobehavioral development, parent-child interaction, as well as parent and child mental and physical health. We include recommendations relevant to adapting in-laboratory assessments for remote data collection and conclude with a description of the successful dissemination of the methods to eight research sites across the United States, each of whom are involved in Phase 1 of the HEALthy Brain and Child Development (HBCD) Study. These remote methods were born out of pandemic-related necessity; however, they have much wider applicability and may offer advantages over in-laboratory neurodevelopmental assessments. Highlights: Novel methods for remote assessment of infant neurobehavior are described. Methodology for remote collection of biospecimens are detailed. Measures of caregiver behavior and maternal perinatal biology are also addressed. These methods have been successfully disseminated across the US as part of HBCD.